ANEMIA PADA REMAJA PUTRI DI SEKOLAH MENENGAH KEJURUAN KESEHATAN BINA PRESTASI TANGERANG - Thoha, Thoha; Subiakto, Toto (Jurnal Medikes (Media Informasi Kesehatan), 2023)
The problem of undernutrition and poor iron and protein nutrition is directly affected by food consumption and infectious diseases and will result in anemia. Want to know the incidence of anemia in young women at SMK Bina Prestasi Health Tangerang. This research uses a descriptive method. It was carried out from September to November 2020. The sampling technique is random sampling using a lottery. Respondents were female adolescents at the Bina Prestasi Health Vocational School, Tangerang, Sukadiri Health Center, Tangerang Regency, with a total sample of 40 respondents. The result, the Fe nutritional adequacy rate is (95%). For young women at Bina Prestasi Health Vocational School in Tangerang, the level of protein nutrition adequacy was (92.5%), and for young women at the Bina Prestasi Health Vocational School in Tangerang who experienced anemia was (42.5%). Those who did not experience anemia were (57.5%).